Statistical inference for type I multiply left-censored samples from Weibull distribution - Fusek, M.; Michalek, J. (Кибернетика и системный анализ, 2019)
Left-censored data with one or more detection limits occur frequently in many application areas. In this paper, the computational procedure for calculation of maximum likelihood estimates of the parameters for type I multiply left-censored data from underlying Weibull distribution is suggested and used considering various numbers of detection limits. The expected Fisher information matrix is analytically determined and its performance is compared with sample (observed) Fisher information matrix using simulations. Simulations are focused primarily on the properties of estimators for small sample sizes. Real data illustration is included. Во многих областях науки часто встречаются задачи с цензурированными слева данными с одной или несколькими границами обнаружения. В данной работе предложена процедура для вычисления оценок максимальной правдоподобности параметров многократного цензурирования слева типа I для распределения Вейбулла с учетом разного числа границ обнаружения. Ожидаемая информационная матрица Фишера определена аналитически и ее вид сравнен с выборочной (наблюдаемой) информационной матрицей Фишера. Моделирование основано, главным образом, на свойствах оценок выборок малых размеров. Примеры проиллюстрированы на реальных данных. У багатьох галузях науки часто зустрічаються задачі з цензурованими зліва даними з однією або кількома межами виявлення. У цій роботі запропоновано процедуру для обчислення оцінок максимальної правдоподібності параметрів багаторазового цензурування зліва типу I з розподілу Вейбулла з урахуванням різної кількості меж виявлення. Очікувану інформаційну матрицю Фішера визначено аналітично та її вигляд порівняно з вибірковою (спостережуваною) інформаційною матрицею Фішера. Моделювання здебільшого ґрунтується на властивостях оцінок вибірок малих розмірів. Приклади проілюстровано на реальних даних.